Effects of Vitamin E From Supplements and Diet on Colonic α- and γ-tocopherol Concentrations in Persons at Increased Colon Cancer Risk - Li, Yiting; Sen, Ananda; Ren, Jianwei; Askew, Leah M; Sidahmed, Elkhansa; Brenner, Dean E; Ruffin, Mack T; Turgeon, D. Kim; Djuric, Zora (Nutrition and cancer, 2015)
The available evidence indicates that γ -tocopherol has more potential for colon cancer prevention than α -tocopherol, but little is known about the effects of foods and supplements on tocopherol levels in human colon. This study randomized 120 subjects at increased colon cancer risk to either a Mediterranean or a Healthy Eating diet for 6 mo. Supplement use was reported by 39% of the subjects, and vitamin E intake from supplements was twofold higher than that from foods. Serum α -tocopherol at baseline was positively predicted by dietary intakes of synthetic vitamin E in foods and supplements but not by natural α -tocopherol from foods. For serum γ -tocopherol, dietary γ -tocopherol was not a predictor, but dietary α-tocopherol was a negative predictor. Unlike with serum, the data supported a role for metabolic factors, and not a direct effect of diet, in governing concentrations of both α - and γ -tocopherol in colon. The Mediterranean intervention increased intakes of natural α -tocopherol, which is high in nuts, and decreased intakes of γ -tocopherol, which is low in olive oil. These dietary changes had no significant effects on colon tocopherols. The impact of diet on colon tocopherols therefore appears to be limited.